Application of Wakalah in International Trade Transactions - Fitri Raya; Dian Febriyani; Elsa Elsa; Rasidah Novita Sari (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
This article will discuss the application of wakalah in the context of letters of credit which are a common means of payment in international trade. This research uses library research (library study). The data source used is secondary data. Secondary data was collected through literature studies related to the application of wakalah contracts in international trade transactions, especially payment systems using letters of credit. This analysis provides insight into how wakalah contracts can be effective instruments and in line with international business needs while maintaining the integrity of Islamic financial values. It is hoped that this research can contribute to further understanding the application of wakalah in international trade transactions, especially in the context of letters of credit, as well as encouraging the development of more inclusive and sustainable business practices.